Distinct modes of stress granule assembly mediated by the KH‐type RNA‐binding protein Rnc1. (17th July 2018) - Satoh, Ryosuke; Hara, Nobuki; Kawasaki, Aki; Takasaki, Teruaki; Sugiura, Reiko
Abstract: We have previously identified the KH‐type RNA‐binding protein Rnc1 as an important regulator of the posttranscriptional expression of the MAPK phosphatase Pmp1 in fission yeast. Rnc1 localization in response to stress has not been elucidated thus far. Here, we report the dual roles of Rnc1 in assembly of stress granules (SGs), nonmembranous cytoplasmic foci composed of messenger ribonucleoproteins. Rnc1 can localize to poly(A)‐binding protein (Pabp)‐positive SGs upon various stress stimuli, including heat shock (HS) and arsenite treatment. Furthermore, Rnc1 deletion results in decreased SGs, indicating that Rnc1 is a new component and a regulator of SGs. Notably, Rnc1 translocates to the dot‐like structures faster than Pabp, and this stress‐induced Rnc1 translocation does not require its RNA‐binding ability, as the Rnc1 KH 1, 2, 3 GD mutant protein with impaired RNA‐binding activity forms dots rather more efficiently than the wild‐type Rnc1 upon HS. Interestingly, in the absence of stress, Rnc1 overproduction induced massive aggregation of Pabp‐positive SGs and eIF2α phosphorylation. In clear contrast, overproduction of the Rnc1 KH 1, 2, 3 GD mutant failed to induce Pabp aggregation and eIF2α phosphorylation, indicating that Rnc1 overproduction‐induced SG assembly requires Rnc1 RNA‐binding activity. Collectively, Rnc1 regulates SG assembly, dependently or independently of its RNA‐binding activity. Abstract : We analyzed the intracellular localization of the KH‐type RNA‐binding protein Rnc1 in relevance to stress responses, and demonstrated that Rnc1 is a novel component and a regulator of stress granules (SGs). We further presented several lines of evidence, suggesting the existence of two distinct modes of SG assembly mediated by Rnc1 with or without its RNA‐binding ability.